Rarefied Flow Simulation of Conical Intake and Plasma Thruster for Very Low Earth Orbit Spaceflight - Ferrato, Eugenio; Giannetti, Vittorio; Tisaev, Mansur; Lucca Fabris, Andrea; Califano, Francesco; Andreussi, Tommaso (Frontiers in Physics, 2022)
Air-breathing electric propulsion has the potential to enable space missions at very low altitudes. This paper introduces to a 0D hybrid formulation for describing the coupled intake and thruster physics of an air-breathing electric propulsion prototype. Model derivation is then used to formally derive the main system key performance indicators and estimate the figure of merit for the design of rarefied flow air intakes. Performance achievable by conical intake shapes are defined and evaluated by Monte Carlo simulations. Influence of inlet flow variation is assessed by dedicated sensitivity analyses. The set of requirements and optimality conditions derived for the downstream plasma thruster suggests concept feasibility within achievable performance range.